Intellectual disability and autism prevalence in Western Australia: impact of the NDIS - Bourke, Jenny; Sanders, Richard; Jones, Jocelyn; Ranjan, Maathumai; Wong, Kingsley; Leonard, Helen (Frontiers in Psychiatry, 2024)
Estimates of the prevalence of intellectual disability or autism spectrum disorder (ASD) may vary depending on the methodology, geographical location, and sources of ascertainment. The National Disability Insurance Scheme (NDIS) in Australia was introduced to provide individualized funding for eligible people with a significant and permanent disability. Its recent inclusion as a source of ascertainment in the population-based Intellectual Disability Exploring Answers (IDEA) database in Western Australia has allowed comparisons of the prevalence of intellectual disability and ASD before and after its introduction. Prevalence of intellectual disability in 2020 was 22.5 per 1,000 (/1,000) live births compared with previous estimates in 2010 of 17/1,000, and for ASD, the estimate was 20.7/1,000 in 2020 compared with 5.1/1,000 in 2010. Whilst the prevalence of ASD in Aboriginal individuals was about two-thirds that of non-Aboriginals, there was an increased prevalence of ASD in Aboriginal children under 10 years compared with non-Aboriginal children. The concurrent relaxation of ASD diagnostic practice standards in Western Australia associated with the administration of access to the NDIS and the release of the National Guidelines empowering single diagnosticians to determine the appropriateness of engaging additional diagnosticians to form a multidisciplinary team on ASD diagnosis, appear to be important factors associated with the increase in ASD diagnoses both with and without intellectual disability.